Knowledge mapping as a technique to support knowledge management in large organisations / Alwi Mohd Yunus … [et al.] - Mohd Yunus, Alwi; Abdul Kadir, Irwan Kamaruddin; Yaacob, Raja Abdullah; Azli Bunawan, AP; Iskandar, Raja Ahmad; Mustaffar, Mohd Yusof (Faculty of Information Management, 2013)
Knowledge is recognized as the most important asset of companies and other organizations. However, the potentials of this commodity have not been fully utilized in line with the growing needs of the k-economy. Knowledge resides in an individual's mind and brain in addition to the explicit knowledge distributed all over the organizations. The need to move towards knowledge management is inevitable and not an option anymore. It is crucial for organizations to be able to tap and map the knowledge within their organizations and this call for the process of defining the knowledge flows and how it could affect the whole range of activities involved in the business and administrative transactions as the basis from which knowledge mapping can be conducted. Knowledge Mapping processes require a team specifically responsible in conducting the mapping procedures. It can be carried out through the whole spectrum of identifying the organizational objectives, addressing the establishment of the experts, documents and the relationship between the various processes. The process of knowledge mapping would then be followed by the capturing of knowledge in the organizations with the ultimate goal of developing the knowledge management program which emphasizes on the culture of knowledge sharing within the organizations. The growth and diversity of knowledge has made the process of knowledge mapping and management a dynamic one.